Revitalisasi Modul Praktikum Anatomi Fisiologi Manusia Berbasis QR Code: Analisis Kebutuhan dan Respon Mahasiswa - Annesha Rahmadayanti; Prendi Niki Halhaji; Rita Rahmayanti; Pani Aswin (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
This study aims to analyze student needs and describe student responses to the limited trial of a revitalized Human Anatomy and Physiology (HAP) laboratory manual integrated with QR Codes as multimedia enrichment access. Revitalization here refers to the comprehensive updating of an existing module, encompassing content substance, procedural instructions, materials alignment, and the addition of digital media via QR Codes. The study employed the ADDIE model; data were collected through four Likert-scale questionnaires and one open-ended evaluation sheet, analyzed descriptively using quantitative and qualitative approaches. Needs analysis involved 57 active students and 23 alumni; the limited trial was conducted with 33 students for one practicum topic due to time constraints. Results showed a very high practicality level with an average student response score of 91.3%. QR Code integration proved effective as a comprehensive pre-lab guide, and qualitative feedback from laboratory assistants confirmed a significant reduction in repetitive technical instruction. This study is limited in scope, covering only one of six practicum topics, and formal expert validation was not conducted.